Dopamine receptor agonists mechanism of actions on glucose lowering and their connections with prolactin actions - Chien, Hung-Yu; Chen, Su-Mei; Li, Wan-Chun (Frontiers in Clinical Diabetes and Healthcare, 2023)
Robust experimental evidence suggests that prolactin can stimulate beta cell proliferation and improve insulin secretion. It also functions as an adipokine to regulate adipogenesis, lipid metabolism and inflammation. Cross-sectional studies reported that higher circulating prolactin levels were associated with greater insulin sensitivity, lower glucose and lipid levels, and lower prevalence of diabetes and metabolic syndrome. The dopamine agonists bromocriptine is approved by FDA for treatment in type 2 diabetes mellitus since 2009. Since prolactin lowering mechanistically leads to suppressed insulin secretion and decreased insulin sensitivity, dopamine agonist should be expected to worsen glucose tolerance. Making it even more complicating, studies exploring the glucose-lowering mechanism of bromocriptine and cabergoline have resulted in contradictory results; while some demonstrated actions independently on prolactin status, others showed glucose lowering partly explained by prolactin level. Studies by Park showed that a moderate increase in central intraventricular prolactin levels improves glucose metabolism with elevated hypothalamic dopamine levels and decreased serum prolactin level. Additionally, sharp wave-ripples from the hippocampus modulates peripheral glucose level within 10 minutes, providing evidence for a mechanistic link between hypothalamus and peripheral blood glucose control. Central insulin in the mesolimbic system have been shown to suppress dopamine levels thus comprising a feedback loop. It appears that dopamine agonists affect glucose homeostasis by 1) affecting central prolactin that increase ventral medial hypothalamic dopamine then through 2) dopamine receptors type 2 signaling/sympathetic activity which 3) act directly on islet and adipocyte, hepatocyte, muscle dopamine receptors type 2 modulate their metabolic effects. The central dopamine and prolactin levels plays a key role in the brain glucose homeostasis control, referring to the pathognomonic central insulin resistance in “ominous octet”, over the serum prolactin level.